EFFECT OF BREXIT ON UNITED KINGDOM'S COMPETITION LAW - Shilpa Bhide-Sahasrabudhe (NLUJ, 2017)
The historical Brexit poll was taken in United Kingdom on June 23, 2016 to decide whether United Kingdom should ‘Remain’ or ‘Leave’ the European Union. ‘Leave’ won the poll and now it is clear that United Kingdom will leave European Union. After the commencement of withdrawal procedure, United Kingdom will negotiate to decide its future relationship with European Union. This exit is going to bring major changes in political, economic and legal structure of United Kingdom. In this article the author will analyze the effect of Brexit on United Kingdom's competition law. Competition law and policy has potential to influence economic growth. Therefore, it is important to find out the effects of Brexit on United Kingdom's competition law. Currently United Kingdom's competition law is vastly based on European Union's competition law therefore after Brexit whether this legal regime will remain same or change partially or completely would depend on the possible option United Kingdom chooses after withdrawal. However one thing is clear that the European Union will be United Kingdom's largest business partner, and therefore it becomes imperative to observe what will be United Kingdom's choice outside European Union.
Keywords: Brexit; United Kingdom competition law; European Union competition law; Post-Brexit legal framework; Economic integration; Trade relations with EU; Competition policy reform; Market regulation; Legal and economic impact of Brexit; UK–EU business relations